Reviving Furcation: Hyaluronic Acid and Xenograft for Grade II Defects - A K Aysha Safoora; Krishnaraj Ganeshnarayanan; K B Uthappa; Rashmi S Pattanshetty (Journal of Multidisciplinary Dental Research)
Furcation involvement in periodontal therapy, particularly in molars, is challenging, and conventional treatments often yield suboptimal results. Advances in understanding inflammation have led to exploring extracellular matrix (ECM) components like hyaluronic acid (HA) to enhance healing and regeneration. To assess the effects of HA combined with xenograft in treating a Grade II furcation defect in a patient with chronic periodontitis. A patient with grade II furcation underwent open flap debridement, receiving a xenograft combined with hyaluronic acid (HA). Radiographic and clinical parameters, including probing pocket depth (PPD), furcation involvement, and bleeding on probing (BOP), were measured at baseline, 6 months, and 9 months. Significant improvements were observed in clinical parameters at the 9-month follow-up: PPD and furcation involvement showed a marked reduction, and BOP decreased. Radiographic evidence indicated substantial bone fill within the defect. The combined use of HA and a bone graft in treating Grade II furcation defects led to improved clinical outcomes and radiographic evidence of bone regeneration. This case report supports the potential of HA as an adjunctive treatment in periodontal therapy for furcation involvement.